RELIGIOUS EDUCATION IN POST-SECULAR SOCIETY - German V. Demidov (Высшее образование в России)
The article is dedicated to the problems of religious education in modern society. The question as to what is the best way (are the best ways) to organize religious education in state-support schools, on theological faculties is now a constant topic of debate. The article brings up some issues of discussion concerning the questions as to how religious education should be organized.